The influence of forest types including native and non‐native tree species on soil macrofauna depends on site conditions - Wenglein, Ronja; Lu, Jing‐Zhong; Scheu, Stefan (Ecology and evolution, 2024)
The ongoing climate change calls for managing forest ecosystems in temperate regions toward more drought‐resistant and climate‐resilient stands. Yet ecological consequences of management options such as planting non‐native tree species and mixing coniferous and deciduous tree species have been little studied, especially on soil animal communities, key in litter decomposition and pest control. Here, we investigated the taxonomic and trophic structure of soil macrofauna communities in five forest types including native European beech (Fagus sylvatica), range‐expanding Norway spruce (Picea abies) and non‐native Douglas fir (Pseudotsuga menziesii) as well as conifer‐beech mixtures across loamy and sandy sites in northern Germany. Abundance of primary decomposers (feeding predominantly on litter) was high in Douglas fir and beech forests, benefiting from less acidic soil and more favorable litter resources compared to spruce forests, while secondary decomposers (feeding predominantly on microorganisms and microbial residues) reached highest densities in spruce forests. Differences in abundance and species richness among forest types generally varied between regions and were most pronounced in Douglas fir of the sandy region. However, trophic guilds differed more between regions than between forest types, indicating that environmental factors outweigh the importance of forest type on soil macrofauna communities. The analysis of stable isotopes (δ15N and δ13C values) supported the general robustness in trophic position of macrofauna trophic guilds against variations in forest types and regions, but indicated reduced detrital shifts and food‐chain lengths in coniferous compared to European beech forests with mixtures mitigating these effects. Overall, for evaluating consequences of future forest management practices on the structure and functioning of soil animal communities, regional factors need to be considered, but in particular at loamy sites the taxonomic and trophic structure of soil macrofauna communities are resistant against changes in forest types.